Fire safety for residential college in higher education: A literature review / Adnin Syaza Jaafar ... [et al.] - Jaafar, Adnin Syaza; Abdul Talib, Yuhainis; Ismail, Asmat; Othman, Muhammad Anas (2022)
A residential college is a building that functions as students’ accommodation. Other than providing an attractive environment that is conducive for learning, it is expected to have functionalities that comply with building standards including the safety features. Fire poses a significant risk to residential college buildings. When a fire occurs, it may cause injuries and deaths as well as losses to university management and occupants. The aim of this paper is to review the literature on issues related to fire safety in a residential college. The objective of this paper is to find the gap on critical factors of fire occurrences in a residential college. This paper uses content analysis methodology to critically review 29 papers. The thematic analysis is adopted by categorising the critical factors into the theme. Results show the four main critical factors which are human, high fire load, design configuration, and facility conditions. The findings suggest that over occupancy and poor means of escape route designs lead to overcrowding and chaos during fire evacuations. The article recommends identifying design criteria of escape routes in residential college buildings for fire-safe buildings.